Conceptual Foundations Of Applying Smart Technologies To The Educational Process - Eshonkulova Madina Nosir kizi (Next Scientists International Journal EIJP, 2026)
In the modern digital environment, increasing educational efficiency, developing students' independent thinking, and ensuring interactivity are among the most pressing issues. This article highlights the conceptual foundations of applying smart technologies to the educational process. The research results demonstrate that the integration of smart technologies increases flexibility, individualization, and quality indicators in the learning process. Based on this, the prospects for the development of smart education will be determined.